Behavioral Paradigms to Evaluate PPAR Modulation in Animal Models of Brain Injury - Greene-Schloesser, Dana (2013)
The use of behavioral testing has become an invaluable tool for assessing the efficacy of therapeutics for a variety of disorders of the central nervous system. This chapter will describe in detail several behavioral paradigms to evaluate the efficacy of PPAR agonists to modulate cognitive impairments in rodent models. When used together as a battery these procedures allow for a global assessment of cognition. These tests are explained in detail below, and include: (1) Novel Object Recognition (NOR), (2) Morris Water Maze (MWM), (3) Delay Match to Place (DMP), and (4) Cue Strategy.